Case studies in private sector participation water supply services. (Metro Manila, Philippines Asian Development Bank, 2017)
Water and wastewater services in Pacific island countries (PICs) include three broad activities: water treatment, water distribution, and wastewater treatment. In most Pacific urban areas, these functions are the responsibility of public sector departments or state-owned enterprises. Water and wastewater services typically require large capital and maintenance expenditure throughout the life of the assets. In the Pacific, capital expenditure is often funded through donor grants and loans, but maintenance expenditure is rarely sufficient to support the useful life of the assets. Water utilities suffer from high rates of nonrevenue water, both from leakage and from low collection rates. Very few water utilities collect enough revenue from users to recover their costs and provide a commercial return.
Keywords: Water supply; Sanitation; Electronic books